Experiences of Students with Communication Related Disabilities in the TBL Classroom - Rachel Berkson; Uwe Matthias Richter; Sarada Veerabhatla; Larysa Zasiekina (East European Journal of Psycholinguistics, 2020)
The objective of this article is to explore how suitable Team-Based Learning (TBL) is for students with social and communication disabilities, such as those on the autism spectrum or with social anxiety. TBL is a structured form of Active Collaborative Learning, combining a flipped classroom approach with students working in permanent teams to apply concepts, models and theories into practice. The design of the study was based on an idiographic case study approach at Anglia Ruskin University, UK, treating each student as an individual rather than a representative sample. Towards the end of the academic year 2017/18, an electronic questionnaire was sent out to all students who had taken TBL modules at ARU during the preceding academic year, asking about various aspects of TBL experience. The questionnaire was repeated towards the end of the first semester of 2018/19. The questionnaire was analysed with a focus on questions relating to inclusivity, and the responses related to students who had declared a disability. The questionnaire was followed by semi-structured interviews with students with disabilities who had experienced TBL. We focused primarily on disabilities broadly related to communication, notably with dyslexia, dysgraphia, social phobia and autism that may impair students’ abilities to work in teams. Interviews were audio recorded and then transcribed. Transcriptions were thematically analysed by the research team using NVivo. The results of the study provide anonymized case studies for each of the students who took part in an interview, explaining their disability or condition, their coping strategies for studying in HE, and their experiences, both positive and negative, of the TBL modules they had taken.